Factors that influence the effective of social media advertising: a study at Netherlands Maritime Institute of Technology (NMIT)/ Nurul Arinah Muhammud - Muhammud, Nurul Arinah (2018)
In era globalization, social media have become convenience to consumers to receive information and knowledge. In recent years, many businessmen have shifted from traditional media platform to social media because they want to minimum cost effective in order to gain maximum profit. Social media advertising continues to change as the usage of social media continues to spread and distribute. This purpose of the study is to identify the factors that influence the effective of social media advertising in Netherlands Maritime Institute of Technology. In this study, the researcher used reliability analysis, Pearson correlation coefficient and regression analysis in order to run the analysis. There are five independents variables and one dependent variable tested which are informativeness, credibility, entertainment, creativity and advertising value. Besides, there are 100 respondents were participating in this study and the researcher used convenience sampling as a sampling technique. The findings indicate that among the five independent variables, only advertising value are significant towards the dependent variable. From the finding, the highest significant relationship is advertising value and contributes highest factors that influence the effective of social media advertising in Netherlands Maritime Institute of Technology.